2017
DOI: 10.1177/1753425917741970
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate enhances intestinal integrity, inhibits mast cell activation, inflammatory mediator production and JNK signaling pathway in weaned pigs

Abstract: The present study aimed to investigate the effects of sodium butyrate on the intestinal barrier and mast cell activation, as well as inflammatory mediator production, and determine whether mitogen-activated protein kinase signaling pathways are involved in these processes. A total of 72 piglets, weaned at 28 AE 1 d age, were allotted to two dietary treatments (control vs. 450 mg/kg sodium butyrate) for 2 wk. The results showed that supplemental sodium butyrate increased daily gain, improved intestinal morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 36 publications
(52 reference statements)
9
42
0
Order By: Relevance
“…The present study demonstrated that oral NaB for 7 weeks did not result in any adverse effects, and animals gained weight normally. In addition, a previous study revealed that NaB enhanced intestinal integrity in weaned pigs (32). Adding NaB increased the food intake of lactating sows and improved the growth of piglets (33).…”
Section: Discussionmentioning
confidence: 93%
“…The present study demonstrated that oral NaB for 7 weeks did not result in any adverse effects, and animals gained weight normally. In addition, a previous study revealed that NaB enhanced intestinal integrity in weaned pigs (32). Adding NaB increased the food intake of lactating sows and improved the growth of piglets (33).…”
Section: Discussionmentioning
confidence: 93%
“…13490 | RSC Adv., 2018,8,[13482][13483][13484][13485][13486][13487][13488][13489][13490][13491][13492] This journal is © The Royal Society of Chemistry 2018…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Mast cell inammatory mediator release (e.g., proteases, histamine and cytokines) plays a major role in the intestinal barrier disruption during the post-weaning period. 7,8 Hence, controlling the intestinal mast cell inammatory mediators release may have benets in alleviating weaning-induced intestinal barrier damage in piglets. Furthermore, weaning can disrupt the oxidative balance and cause oxidative injury in the small intestine of piglets, so maintaining the antioxidant capacity is also crucial in preserving intestinal integrity.…”
Section: Introductionmentioning
confidence: 99%
“…This has treatment implications, including the use of sodium butyrate, which maintains the gut barrier and attenuates the stress-induced increase in proinflammatory cytokines from mucosal mast cells that underpin psychological stress-induced gut permeability. 56 2.9 | Autonomic nervous system and alpha 7 nicotinic receptor…”
Section: Gut Microbiomementioning
confidence: 99%